Analysis of Remote Access Trojan Attack using Android Debug Bridge - Deco Aprilliansyah; Imam Riadi; Sunardi (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
The security hole in the android operating system sometimes not realized by users such as malware and exploitation by third parties to remote access. This study conducted to identify the vulnerabilities of android operating system by using Ghost Framework. The vulnerability of the android smartphone are found by using the Android Debug Bridge (ADB) with the exploitation method as well as to analyze the test results and identify remote access Trojan attacks. The exploitation method with several steps from preparing the tools and connecting to the testing commands to the testing device have been conducted. The result shows that android version 9 can be remote access by entering the exploit via ADB. Some information has been obtained by third parties, enter and change the contents of the system directory can be remote access like an authorized to do any activities on the device such as opening lock screen, entering the directory system, changing the system, etc.